IDEAL TEACHER AND STUDENT IMAGE IN AYTMATOV’S FIRST TEACHER NOVEL: DÜYŞEN AND ALTINAY - Durukoğlu, S.; Cömert, Ç. (Journal of Oriental Studies, 2022)
In Aytmatov’s novel, My First Teacher, the difficulties experienced by the Kyrgyz in the transition from verbal and natural education to formal education, brought about by the nomadic life, are explained through the characters of teacher Düyşen and his student Altınay Süleymanovna. Aytmatov’s ideal is to create well-educated, modern Kyrgyz people, without discriminating between men and women. This project makes it necessary to execute the mental change that will mean a total revolution, to break the negative influence of the tradition and to bring forth role models. In the novel, the characters of teacher Düyşen and female student Altınay were fictionalized as role models who will achieve this job by creating a new life against the past and living and spreading it. Despite of his lacking qualifications to be a proper teacher, Düyşen touches his students’ lives with the sacrifices he makes for them. Düyşen, who struggles with both the people against education and physical inadequacies, never gives up. As a woman, Altınay takes her share of a woman’s luck, being tortured by her aunt, forced to wed an already married man at the age of fifteen, but she still never stops fighting for herself. Düyşen achieves the ideal of Aytmatov by improving through his insufficient teaching, and his student Altınay as a well-known and respected professor. In this study, educational, cultural issues and financial problems mentioned in the novel; the ideal teacher and student image, and through Altınay, the woman’s ability to overcome her misfortune due to inequality of opportunity to make a new life and order possible for herself will be focused upon. Document analysis and descriptive scanning model, among qualitative research methods, are used in the study.